Insensitivity of calcium-dependent endothelial stimulation in rat isolated aorta to the calcium entry blocker, flunarizine. - Miller, R. C. (1985)
In rat aortic segments complete with endothelium, acetylcholine (1 microM) relaxed noradrenaline, phenylephrine and prostaglandin F2 alpha (PGF2 alpha)-induced contractions of various magnitudes. Maximal 1 microM phenylephrine-induced contractions were relaxed to a greater extent than were maximal contractions induced by the other two agonists. Contractions elicited by various concentrations of phenylephrine and PGF2 alpha in the presence of a maximal effective concentration of the calcium entry blocker flunarizine (3 microM) were relaxed by acetylcholine to about the same residual tension as were contractions elicited in the absence of flunarizine. Acetylcholine (1 microM) and phenylephrine (1 microM) increased tissue levels of guanosine cyclic 3'5'-monophosphate (cyclic GMP) by about 37 fold and 2 fold respectively. Preincubation of tissues in the absence of calcium abolished these agonist-induced increases in cyclic GMP levels, but preincubation with flunarizine had no significant effect on the increase in cyclic GMP level induced by the agonists. Pretreatment with flunarizine had no significant effect on the basal tissue level of cyclic GMP, but pretreatment in calcium-free solution reduced the basal tissue level of the cyclic nucleotide by about half. It is concluded that in rat aorta, endothelium-dependent acetylcholine-induced relaxation and endothelium-dependent acetylcholine and phenylephrine-induced increases in tissue levels of cyclic GMP, are dependent on extracellular calcium, but are not antagonized by flunarizine. This may indicate that if calcium channels of endothelial cells are activated by these agonists, their characteristics are not identical with those of the calcium channels of the smooth muscle cells.